PENAPISAN VIRTUAL SENYAWA TURUNAN METIL SINAMAT PADA ENZIM SIKLOOKSIGENASE-2 (COX-2 - Teni Ernawati (Research Center for Chemistry - LIPI, 2012)
Inflammation is the response of living tissue to vascular injury. Non-Steroid Anti-Inflammatory Drugs(NSAIDs) could control pain caused by inflammation. Therapeutic effects of NSAIDs are related to themechanism of the cyclooxygenase-1 (COX-1) enzyme and the cyclooxygenase-2 (COX-2) enzyme in inhibiting theproduction of prostaglandins. In this paper, we report the virtual screening of methyl cinnamate derivativecompounds against the COX-2. All methyl cinnamate derivative compounds were molecular docking simulatedusing the Protein-Ligand ANT System (PLANTS) software with ZINC03814717 as the reference compound. Fromthe results of virtual screening, it was obtained that derivative compounds of methyl cinnamate were predicted asactive COX-2 inhibitors because they have ChemPLP score better than that of the reference compoundsZINC03814717. The compound of acid 3- (4-benzoylphenyl) propionate was predicted as having the best score ofChemPLP.Keywords: Non-Steroid Anti-Inflammatory (NSAID), virtual screening, enzyme cyclooxygenase-2 (COX-2), methyl cinnamate derivative